Kesetaraan di Hadapan Allah: Laki-laki dan Perempuan dalam Al-Qur’an - Adzima, Fauzan (Pusat Studi Wanita UIN Ar-Raniry, 2025)
Equality in Islam is a fundamental principle that asserts men and women have the same status before Allah in terms of faith and righteous deeds. This concept does not imply identical roles but emphasizes the value and rewards granted by Allah based on one's actions. This study examines the concept of equality in Islam through a tafsir-based approach to QS. Al-Ahzab (33:35) and QS. An-Nahl (16:97). The findings indicate that in Islam, both men and women who embody qualities of faith, such as piety, patience, and sincerity in worship, will receive equal rewards, including forgiveness, paradise, and happiness in both this world and the hereafter. Islam does not restrict individuals based on gender but instead emphasizes justice in rights and responsibilities according to their natural disposition. Thus, the principle of equality in Islam is not merely about identical roles but represents divine justice, offering every individual an equal opportunity to attain true happiness. This study recommends broader education on this concept to prevent misconceptions and biases, ensuring its proper implementation in society in alignment with Islamic values.